2015
DOI: 10.1126/scisignal.aab2425
|View full text |Cite
|
Sign up to set email alerts
|

The kinases NDR1/2 act downstream of the Hippo homolog MST1 to mediate both egress of thymocytes from the thymus and lymphocyte motility

Abstract: The serine and threonine kinase MST1 is the mammalian homolog of Hippo. MST1 is a critical mediator of the migration, adhesion, and survival of T cells; however, these functions of MST1 are independent of signaling by its typical effectors, the kinase LATS and the transcriptional coactivator YAP. The kinase NDR1, a member of the same family of kinases as LATS, functions as a tumor suppressor by preventing T cell lymphomagenesis, which suggests that it may play a role in T cell homeostasis. We generated and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 54 publications
2
60
0
Order By: Relevance
“…Considering further that STK38 knockout mice are viable and fertile with normal life spans [28, 56] and STK38 displays unique features in its regulatory and catalytic domains [26, 27], we propose that the development of pharmacological compounds that selectively target STK38 should be a feasible option for clinical approaches aiming to target “autophagy addicted” cancers. However, STK38 inhibitors will require stringent evaluation, since STK38 has other cellular functions [27] besides the roles described here, and STK38-deficiency can impair the immune system of mice [28, 57, 58]. Thus, it will be interesting to ascertain in appropriate preclinical cancer models whether selective and acute STK38 inhibition can be of therapeutic benefit to target Ras-driven cancer cells without harming healthy tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Considering further that STK38 knockout mice are viable and fertile with normal life spans [28, 56] and STK38 displays unique features in its regulatory and catalytic domains [26, 27], we propose that the development of pharmacological compounds that selectively target STK38 should be a feasible option for clinical approaches aiming to target “autophagy addicted” cancers. However, STK38 inhibitors will require stringent evaluation, since STK38 has other cellular functions [27] besides the roles described here, and STK38-deficiency can impair the immune system of mice [28, 57, 58]. Thus, it will be interesting to ascertain in appropriate preclinical cancer models whether selective and acute STK38 inhibition can be of therapeutic benefit to target Ras-driven cancer cells without harming healthy tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The emerging roles of Mst1/Mst2 in lymphocyte trafficking, adhesion, and cell polarity are distinct from the canonical Hippo-LATS-YAP pathway to restrain cell proliferation and are consistent with phenotypes of MST1 mutations identified in human immunodeficiencies with recurrent infection and autoantibody production (35). Recently, several regulators downstream of Mst1/Mst2 that mediate lymphocyte trafficking were reported, including DOCK8 (34), Rab13 (36), and LATS homolog NDR kinases (37). However, the role of TCR-triggered Rap1 signaling to Mst1 for LFA-1 activation and formation of the IS remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of the hydrophobic motif is mediated by upstream Ste20-like kinases: MST1/2 for LATS1/2 and NDR1/2 (Chan et al 2005;Vichalkovski et al 2008;Hergovich et al 2009;Tang et al 2015), and MST3 for NDR1/2 (Stegert et al 2005). Recent studies have shown that MAP4Ks, also members of the Ste20 family, can phosphorylate the LATS1/2 hydrophobic motif Zheng et al 2015).…”
Section: Mechanisms Of Hippo Kinase Cascade Activationmentioning
confidence: 99%
“…MST1/2 are known to phosphorylate a number of other "non-Hippo" proteins in addition to LATS1/2, SAV1, and MOB1A/B. For instance, NDR1/2 are reported to be MST1/2 substrates that regulate thymocyte egress and T-cell migration (Vichalkovski et al 2008;Tang et al 2015). MST1/2 can phosphorylate FOXO1 to promote its nuclear localization and transcription of genes promoting apoptosis in mammalian neurons (Lehtinen et al 2006).…”
Section: Redefining the Hippo Pathwaymentioning
confidence: 99%